Challenges in Diagnosing and Managing Self-Embedding Behavior: A Rare Case Report - Ahuja, Priya; Goyal, Divakar (Medical Science: Trends and Innovations Vol. 4, 2025)
Objectives: Self-embedding behavior (SEB) is a complex phenomenon characterized by the deliberate insertion of objects into soft tissues, often associated with psychotic or factitious disorders. Commonly used objects include needles, staples, pins, spikes, and pieces of wire. This study aims to highlight the clinical challenges and management of SEB through a rare case presentation. Methods: The case of a 25-year-old male who presented with SEB involving the insertion of a knitting needle approximately 10 cm into his left gluteal region through a pre-existing gluteal abscess, was reported. The patient was successfully treated with surgical intervention and multidisciplinary care. Results: The foreign body was successfully removed without post-operative complications. The patient was observed postoperatively, underwent psychiatric evaluation, and was monitored for six months, demonstrating no recurrence or long-term complications. Conclusion: SEB is a multifaceted condition with significant medical, psychiatric, and legal implications. Early recognition, timely intervention, and interdisciplinary collaboration between trauma surgeons, psychiatrists, and legal experts are critical to ensuring optimal patient outcomes and preventing severe complications.